235k views
1 vote
G(x) =3x-1 find g(2)

2 Answers

2 votes
answer: 5

step by step:
okay so to do this you plug in 2 for x
g(2)=3(2)-1

then multiply 3 by 2
3*2=6

that makes g(2)=6-1

6-1=5

g(2)=5
User Bab
by
4.6k points
5 votes

Answer:

The value of g(2) would be 5.

Explanation:

Here, the given function,


g(x) = 3x - 1,

By substituting x = 2 in the above equation,

We get,


g(2) = 3(2) - 1


g(2) = 6 - 1 ( By multiplication )


g(2) = 5 ( by subtraction )

Hence, the value of g(2) would be 5.

User Matthew Lewis
by
5.6k points